Sosialisasi Hukum Tentang Faktor dan Dampak Perkawinan Usia Muda di Kelurahan Talotenreng Kabupaten Wajo - Andi Dadi Mashuri Makmur; Martono; Firman; Riska Apriyani; Feby Adriyanti; Devi Ratnasari; Agus Salim; Surahman (Compile Journal of Society Service, 2025)
Several studies and socializations on the factors and impacts of early marriage have been conducted in several villages and sub-districts in Wajo Regency because this is included in the work program that has become one of the main concerns of the Wajo Regency government as stated in Regent Regulation No. 64 of 2022, concerning the prevention and handling of child marriage. The urgency of this problem is because it has placed Wajo Regency as one of the regencies in South Sulawesi with a fairly high rate of early marriage in the last 3 (three) years. Although there has been a decrease in the rate of early marriage by 6.29 percent (BPS, 2023), there were still 82 applicants for child marriage in 2023 based on data from the UPTD for the Protection of Women and Children (PPA) DP2KBP3A, Wajo Regency Social Service. Therefore, this research and community service are needed to conduct socialization on the factors and impacts of early marriage in Talotenreng Village, Wajo Regency, in addition to playing a role in assisting the government in reducing the rate of early marriage, it also aims to increase public legal awareness and the impacts of early marriage.